Effective synthesis of cyclic carbonates from CO2 and epoxides catalyzed by acetylcholine bromide-based deep eutectic solvents. (April 2022) - Yang, Xiaoqing; Liu, Zimin; Chen, Peng; Liu, Fei; Zhao, Tianxiang
Abstract: Fixing CO2 into cyclic carbonates is urgently required under green and eco-friendly conditions. Herein, we synthesized a series of bio-based deep eutectic solvents (DESs) for catalyzing cycloaddition reaction of CO2 with epoxides. Notably, AcChBr-LMA (2:1) formed by acetylcholine bromide (AcChBr) and L -malic acid (LMA) shows the best catalytic activity (up to 98% yield) and excellent recyclability under mild conditions (0.1 MPa CO2 pressure, 80 °C and 2 h). Mechanism studies have shown that there is a synergistic catalytic effect between the hydrogen bond acceptor (HBA) and hydrogen bond donor (HBD). Highlights: Acetylcholine bromide-based DESs are used as efficient catalysts for CO2 conversion. AcChBr-LMA (2:1) can be recycled without significant loss of activity. Mechanistic studies reveal synergistic catalysis to promote cycloaddition of CO2 and epoxides.